On the Universality of the Universal Declaration of Human Rights - Luis Bueno Ochoa (Ius Humani. Jornal do direito, 2023)
The Universal Declaration of Human Rights (UNO, 1948) took place very shortly after the end of the Second World War and therefore emerged in a context that we associate with the dawn of the so-called Cold War. Almost seventy-five years after that date, the changes, often disruptive, have come on the back of what is known as the Digital Revolution, also called the Third Industrial Revolution or the Scientific and Technological Revolution, which includes the all-encompassing phenomenon of Globalisation. The universalisation of human rights may collide with other relativistic visions, such as interculturality or multiculturalism, for example. The commonly asserted characteristics of human rights, i.e. that they are objective, absolute and unalienable, may not be conclusive. The note of diversity disseminated by bodies such as UNESCO makes this clear: the celebration of the World Day for Cultural Diversity for Dialogue and Development, organised by UNESCO every 21 May, highlights, in this sense, not only the richness of the world's cultures but also the essential role of intercultural dialogue in achieving peace and sustainable development without detracting from its economic value. In this context, how can we reconcile universality and diversity? And without abandoning the tolerance-dignity binomial, let us continue to ask ourselves whether the universality that is being proclaimed is intended to impose a markedly Western worldview.